Aircraft Disasters- roles of materials (2009)
Aircraft disaster has been in existence since air was conquered by man as a means of transportation. 487.5 million and 874.4 millions of cumulative departures and flight hours respectively have been estimated since 1959. Analysis of aircraft failure based on 5,149 on-board fatalities recorded shows that 13% of total aircraft accident was caused by mechanical failure while loss of control was responsible for over 31% of onboard fatalities. Aircraft accident is known to be most fatal during take-off and landing phase contributing about 49% while onboard fatality during cruise is about 19%. In this work, reviews of aircraft disasters were made via Fractographic examination, SEM and finite element modeling. It must be stated that few of aircraft failures which are not material related are not considered in this review. The review focused on material related failure which have been analyzed, accepted and published in reputable journals.